MODAL SOSIAL DAN KARAKTERISTIK PETANI KACANG TANAH DI DESA KANONANG 1 DAN 3 KECAMATAN KAWANGKOANThe objective of the research is to know social capital and peanuts farmer characteristics at Kanonang 1 and 3 villages , Kawangkoan District. The research usi - Fenny L.B. Umbas (COCOS, 2012)
The objective of the research is to know social capital and peanuts farmercharacteristics at Kanonang 1 and 3 villages , Kawangkoan District. The research usingpurpose sampling method in peanut farmer at Kanonang 1 and 3 villages, with 20respondent farmers from Kanonang 1 and 15 respondent farmers from Kanonang 3village.Variable that measurement in this research is social capital that consists of trust, norm,link. Farmer characteristics, such as age, education and experience in farming.The result of the research showed that relation between social capital and farmercharacteristics such as age, existence in social capital scale was sufficient, social capitaland farmer characteristics relation such as education existence in social model scale washigh, social capital and farmer charactistics relation such as experience existence in socialcapital scale was high. Thus, social capital peanut farmer in Kanonang 1and 3 villageexistence in social capital scale was high.Keywords : Social Capital, Characteristics, Farmer, Trust, Norm, Link